Rock core particle gravity flow deposition film as well as preparation method and application thereof

By preparing the gravity flow deposition film of core particles, the error and complex operation problems of existing reservoir percolation research methods are solved, and accurate analysis and simple detection of the core percolation characteristics of the reservoir are achieved.

CN119534258AActive Publication Date: 2025-02-28PETROCHINA CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311106961.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-30
Publication Date
2025-02-28
Estimated Expiration
2043-08-30

AI Technical Summary

Technical Problem

The existing reservoir infiltration research methods have errors and inconveniences, and it is impossible to effectively measure the volume of crude oil attached to the core surface, and the operation is complicated and time-consuming.

Method used

The preparation method of gravity flow deposition film of core particles is adopted, and the core nanoparticles are obtained by grinding and screening. After mixing water, it forms a suspension, and transferred to a solid matrix plate and allowed to precipitate and dry on a solid substrate to form a deposition film.

Benefits of technology

It realizes accurate analysis of the core permeability characteristics of reservoirs, simplifies the operation process, improves the accuracy and stability of detection, and is suitable for reservoir wettability and permeability research.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119534258A_ABST
    Figure CN119534258A_ABST
Patent Text Reader

Abstract

The invention provides a rock core particle gravity flow deposition film and a preparation method and application thereof, and the preparation method comprises the following steps: (1) grinding and screening rock core particles in sequence to obtain rock core nanoparticles; (2) mixing water with the core nanoparticles obtained in the step (1) to obtain a turbid liquid; and (3) transferring the turbid liquid obtained in the step (2) to a solid substrate plate, standing and precipitating, and drying to obtain the rock core particle gravity flow deposition film. According to the rock core particle gravity flow deposition film provided by the invention, accurate analysis of reservoir rock core imbibition characteristics can be realized, and the rock core particle gravity flow deposition film has a wide application scene in the field of oil reservoir wettability and imbibition research.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oil reservoir production engineering, and in particular relates to a core particle gravity flow deposition film and a preparation method and application thereof. Background Art

[0002] The main methods for studying the imbibition of storage reservoirs include volumetric method, mass method, nuclear magnetic resonance method, CT scanning method, etc., which are all experimental means currently used in the field of reservoir engineering to study the storage imbibition characteristics.

[0003] The volumetric method uses an Amott imbibition bottle to measure the volume of the produced crude oil and obtain the final imbibition recovery rate. The device is divided into two parts, the upper part is a capillary metering tube with a scale, and the lower part is a transparent glass container. The produced crude oil floats to the capillary metering tube through buoyancy, and the imbibition recovery rate can be calculated by measuring the volume of crude oil. This method is simple to operate and can carry out imbibition experiments in batches. It is currently the most widely used imbibition experiment method. Its disadvantages are that it is limited by the container volume and scale range, which affects the experimental results, and it is impossible to measure the volume of crude oil attached to the rock surface.

[0004] In order to solve the defect of the volume method that the volume of crude oil attached to the rock surface cannot be measured, Pu Yu and others designed an imbibition experimental method to calculate the volume of oil produced by imbibition through mass change. The basic principle of the experiment is that the wetting phase such as water and the non-wetting phase such as oil in the core undergo imbibition replacement, and there is a density difference between oil and water, which can quantitatively analyze the degree of imbibition recovery. During the experiment, the change of core weight is mainly monitored in real time by an electronic balance, which is convenient and fast. However, due to the large amount of crude oil attached to the rock surface, a measurement error of more than 100% of the imbibition recovery rate may occur.

[0005] The nuclear magnetic resonance method uses the resonance characteristics of hydrogen atoms under the action of a magnetic field to clarify the distribution of fluids in rock pores. This method can obtain grayscale images of oil and water distribution without destroying the core morphology, calculate the change in oil saturation, and obtain the imbibition recovery rate. It is more accurate and obtains more comprehensive information than the previous two methods, but it is more complicated to operate and has a higher testing cost.

[0006] The CT scanning method uses X-rays to irradiate the target core, and combines the principle of ray attenuation to perform three-dimensional distribution of the core, which can quantitatively analyze the porosity value and porosity distribution of the core under different conditions. Compared with the aforementioned volume method and mass method, the CT scanning method can better avoid the errors in the volume method and mass method experiments because the measurement tools involved are not in direct contact with the rock. However, the CT scanning method also has disadvantages such as high cost and long experimental time.

[0007] Based on the above application and testing characteristics, it is necessary to improve the existing reservoir imbibition method so that the imbibition characteristics of the research are obvious and more stable, making the means of studying the imbibition characteristics of the reservoir core more reliable and broadening its application scope.

[0008] In addition, in previous core-based imbibition studies, there are relatively few methods that can be used to quickly detect the imbibition of core samples. As we all know, when pre-treating cores, the process of core processing required by the staff is very complicated and takes a long time. Therefore, to solve this problem, it is necessary to develop a portable core permeability characteristic research method and establish a set of accurate, fast, simple and economically feasible detection methods. Among them, the flattening of the core is the key to solving the above contradictions. Summary of the invention

[0009] In view of the shortcomings of the prior art, the present invention aims to provide a core particle gravity flow deposition film and its preparation method and application. The core particle gravity flow deposition film can realize accurate analysis of the imbibition characteristics of reservoir cores and has broad application scenarios in the field of reservoir wettability and imbibition research.

[0010] To achieve this object, the present invention adopts the following technical solutions:

[0011] In a first aspect, the present invention provides a method for preparing a core particle gravity flow deposition film, the preparation method comprising the following steps:

[0012] (1) grinding and screening the core particles in sequence to obtain core nanoparticles;

[0013] (2) mixing water and the core nanoparticles obtained in step (1) to obtain a suspension;

[0014] (3) The suspension obtained in step (2) is transferred to a solid matrix plate, and after static precipitation and drying, the core particle gravity flow deposition film is obtained.

[0015] The method for preparing the core particle gravity flow deposition film provided by the present invention is simple and convenient, and can realize accurate analysis of the imbibition characteristics of the reservoir core.

[0016] The core particles in step (1) of the present invention are derived from a certain area outside Daqing, which is the research target area, and the core sampling depth is 1800.9-1896.1m.

[0017] As a preferred technical solution of the present invention, step (1) further includes a crushing process before grinding.

[0018] Preferably, the mass ratio of core particles to grinding balls during grinding is 3:(4-6), for example, 3:4, 3:4.03, 3:5 or 3:6, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0019] Preferably, the grinding rotation speed is 300-500 r / min, for example, it can be 300 r / min, 350 r / min, 400 r / min, 450 r / min or 500 r / min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0020] Preferably, the grinding time is 240 to 280 min, for example, 240 min, 250 min, 260 min, 270 min or 280 min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0021] It is worth noting that the crushing in the present invention is to crush the core into 1 cm 3 The grinding process is as follows: a vertical planetary ball mill (YXQM-0.4L) is used to grind the crushed core particles, and the grinding cycle is that the grinder is stopped for 5 minutes every 30 minutes; the number of large, medium and small grinding balls is 1:2:10 respectively, wherein the small ball is a zirconia ball with a diameter of 5 mm and a single gram weight of 0.25 g, the medium ball is a zirconia ball with a diameter of 10 mm and a single gram weight of 0.33 g, and the large ball is a zirconia ball with a diameter of 15 mm and a single gram weight of 0.86 g; the screening is carried out by using a laser particle size analyzer (Mastersizer3000) for particle size confirmation and screening.

[0022] Preferably, the particle size of the core nanoparticles in step (1) is 500-3000 nm, for example, 500 nm, 1000 nm, 1500 nm, 2000 nm, 2500 nm or 3000 nm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0023] As a preferred technical solution of the present invention, the usage ratio of water and core nanoparticles in step (2) is 30mL:(0.1-0.5)g, for example, it can be 30mL:0.1g, 30mL:0.2g, 30mL:0.3g, 30mL:0.4g or 30mL:0.5g, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0024] Preferably, the mixing in step (2) comprises ultrasonic mixing.

[0025] Preferably, the ultrasonic mixing time is 20 to 40 min, for example, 20 min, 25 min, 30 min, 35 min or 40 min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0026] Preferably, the power of the ultrasonic mixing is 80-120 W, for example, 80 W, 90 W, 100 W, 110 W or 120 W, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0027] Preferably, the frequency of the ultrasonic mixing is 30-50 kHz, for example, 30 kHz, 35 kHz, 40 kHz, 45 kHz or 50 kHz, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0028] The purpose of the ultrasonic mixing of the present invention is to prevent the core particles from agglomerating in water and to fully disperse the core particles in water.

[0029] It is worth noting that in order to make the core particle gravity flow deposition film closer to the mineralization conditions of the actual formation, the preparation method of the present invention also includes adding metal ion solution or pure water to the suspension in step (2).

[0030] As a preferred technical solution of the present invention, the size of the solid matrix plate in step (3) is (2-3) cm×(3-5) cm, for example, 2.5 cm×4 cm, 2 cm×5 cm, 2 cm×3 cm, 2.5 cm×4.5 cm or 3 cm×3.5 cm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0031] Preferably, the solid substrate plate in step (3) comprises any one of quartz, hydrophilic glass or quartz glass.

[0032] The solid substrate plate of the present invention is a transparent, impermeable solid substrate.

[0033] As a preferred technical solution of the present invention, the transfer in step (3) comprises: extracting the suspension obtained in step (2) and injecting it onto the solid matrix plate.

[0034] Preferably, the extraction volume of the suspension is 1.0-3.0 mL, for example, 1.0 mL, 1.5 mL, 2 mL, 2.5 mL or 3 mL, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0035] As a preferred technical solution of the present invention, the instrument used in the transfer in step (3) includes a dual-channel pump or a syringe.

[0036] It is worth noting that the dual-channel pump described in the present invention is a FUSION 100 microfluidic infusion syringe pump dual-channel syringe pump; the syringe is a conventional 10 mL syringe for laboratory use.

[0037] Preferably, the injection rate is 0.8-1.5 mL / min, for example, 0.8 mL / min, 0.8 mL / min, 1.0 mL / min, 1.1 mL / min, 1.2 mL / min, 1.3 mL / min, 1.4 mL / min or 1.5 mL / min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0038] The injection rate of the present invention is 0.8-1.5 mL / min. If the injection rate is too high, the mixed suspension will form a jet with an initial velocity, which will impact the deposited liquid film and fail to achieve stable and uniform deposition of particles. If the injection rate is too low, the local deposited film will evaporate and dry first, and cracks will appear in the horizontal film.

[0039] As a preferred technical solution of the present invention, the temperature of the static precipitation is 20-30°C, for example, it can be 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C or 30°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0040] Preferably, the solid matrix plate is placed horizontally during the static sedimentation.

[0041] Preferably, the static sedimentation time is 22 to 28 hours, for example, it can be 22 hours, 23 hours, 24 hours, 25 hours, 26 hours, 27 hours or 28 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0042] It is worth noting that, during the static sedimentation process described in the present invention, it is necessary to ensure that the ambient air is undisturbed and the laboratory table is vibration-free, so as to ensure that the particle deposition is stable and undisturbed.

[0043] As a preferred technical solution of the present invention, the preparation method includes pre-treating the solid matrix plate in step (3).

[0044] Preferably, the pretreatment comprises: washing and drying the solid matrix plate in sequence.

[0045] The purpose of the pretreatment described in the present invention is to clean the dust on the solid substrate and perform drying treatment, which is beneficial for dispersing and spreading the liquid in a uniform and stable form when injecting the mixed suspension, avoiding the attraction of dust and particulate matter to the liquid film, forming local circulation and uneven liquid film.

[0046] As a preferred technical solution of the present invention, the method for preparing a core particle gravity flow deposition film provided in the first aspect of the present invention comprises the following steps:

[0047] (1) Crushing, grinding and screening the core particles in sequence to obtain core nanoparticles with a particle size of 500 to 3000 nm;

[0048] Wherein, the grinding speed is 300-500 r / min, and the grinding time is 240-280 min;

[0049] (2) ultrasonically mixing water and the core nanoparticles obtained in step (1) at a ratio of 30 mL:(0.1-0.5) g to obtain a suspension;

[0050] The ultrasonic mixing time is 20 to 40 minutes, the power is 80 to 120 W, and the frequency is 30 to 50 kHz;

[0051] (3) transferring the suspension obtained in step (2) to a solid substrate plate having a size of (2-3) cm×(3-5) cm, allowing it to settle and dry to obtain the core particle gravity flow deposition film;

[0052] The transferring comprises: extracting 1.0 to 3.0 mL of the suspension obtained in step (2), and injecting the extract onto the solid matrix plate at a rate of 0.8 to 1.5 mL / min;

[0053] The temperature of the static precipitation is 20-30° C. and the time is 22-28 hours. During the static precipitation, the solid matrix plate is placed horizontally.

[0054] In a second aspect, the present invention provides a core particle gravity flow deposited film, wherein the core particle gravity flow deposited film is obtained by the preparation method provided in the first aspect.

[0055] The thickness of the core particle gravity flow deposition film is 1.5×10 5 ~5.5×10 5 nm, for example, 1.5×10 5 nm, 2.5×10 5 nm, 3.5×10 5 nm, 4.5×10 5 nm or 5.5×10 5 nm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0056] The thickness of the core particle gravity flow deposition film of the present invention is 1.5×10 5 ~5.5×10 5If the deposited film is too thick, the surface of the deposited film will be uneven, the surface pores will vary greatly, and the test droplets will penetrate into the deposited film, making it difficult to measure; if the deposited film is too thin, the number of local particles will be small, and the liquid will be easily attracted by the hydrophilic glass matrix of the bottom layer.

[0057] In a third aspect, the present invention provides an application of a core particle gravity flow deposited film as provided in the second aspect, wherein the core particle gravity flow deposited film is used to detect and analyze the dialysis wetting characteristics of an oil reservoir.

[0058] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0059] Compared with the prior art, the present invention has the following beneficial effects:

[0060] (1) The core particle gravity flow deposition film provided by the present invention can realize accurate analysis of the imbibition characteristics of reservoir cores and has broad application scenarios in the field of reservoir wettability and imbibition research;

[0061] (2) The core particle gravity flow deposition film provided by the present invention is a two-dimensional thin layer. Directly detecting the imbibition characteristics on the two-dimensional thin layer core plane can also improve the accurate capture of the imbibition characteristics detection, improve the stability and reliability of the measurement, and expand the application range of the core film;

[0062] (3) The core particle gravity flow deposition film provided by the present invention can be used to directly detect the imbibition characteristics of the reservoir core in the laboratory observation system, eliminating the pre-treatment processes such as sample preparation and sampling, and can achieve accurate detection of the samples to be tested. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] Figure 1 is an electron microscope image of a core particle gravity flow deposited film provided in Example 3 of the present invention;

[0064] Figure 2 is a graph showing the height variation of the core particle gravity flow deposited film in the X (horizontal) direction provided by Examples 3-7 of the present invention;

[0065] Figure 3 It is a schematic diagram of the change process of the wetting angle captured in the X (horizontal) direction by the gravity flow deposition film of the core particles provided in Example 3 of the present invention. DETAILED DESCRIPTION

[0066] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0067] The sources of some components in the following examples and comparative examples are as follows:

[0068] Example 1

[0069] This embodiment provides a core particle gravity flow deposition film, and the preparation method of the core particle gravity flow deposition film comprises the following steps:

[0070] (1) Crushing, grinding and screening the core particles in sequence to obtain core nanoparticles with a particle size of 500 nm;

[0071] Wherein, the grinding speed is 400r / min and the grinding time is 250min;

[0072] (2) ultrasonically mixing water and the core nanoparticles obtained in step (1) at a ratio of 30 mL:0.3 g to obtain a suspension;

[0073] The ultrasonic mixing time is 30 min, the power is 100 W, and the frequency is 40 kHz;

[0074] (3) The suspension obtained in step (2) was transferred to a quartz glass with a size of 2.5 cm × 4 cm, and after being allowed to settle and dried, a quartz glass with a thickness of 1.5 × 10 5 nm core particle gravity flow deposition film;

[0075] The transferring comprises: extracting 2.5 mL of the suspension obtained in step (2) and injecting it onto the solid matrix plate at a rate of 1 mL / min;

[0076] The temperature of the static precipitation is 30° C. and the time is 24 hours. During the static precipitation, the solid matrix plate is placed horizontally.

[0077] Example 2

[0078] This embodiment provides a core particle gravity flow deposition film, and the preparation method of the core particle gravity flow deposition film comprises the following steps:

[0079] (1) Crushing, grinding and screening the core particles in sequence to obtain core nanoparticles with a particle size of 3000 nm;

[0080] Wherein, the grinding speed is 500r / min and the grinding time is 280min;

[0081] (2) ultrasonically mixing water and the core nanoparticles obtained in step (1) at a ratio of 30 mL:0.5 g to obtain a suspension;

[0082] The ultrasonic mixing time is 40 min, the power is 120 W, and the frequency is 50 kHz;

[0083] (3) The suspension obtained in step (2) was transferred to a quartz glass with a size of 2.5 cm × 4 cm, and after being allowed to settle and dried, a quartz glass with a thickness of 5.5 × 10 5 nm core particle gravity flow deposition film;

[0084] The transferring comprises: extracting 2 mL of the suspension obtained in step (2) and injecting it onto the solid matrix plate at a rate of 0.8 mL / min;

[0085] The temperature of the static precipitation is 25° C. and the time is 28 h. During the static precipitation, the solid matrix plate is placed horizontally.

[0086] Example 3

[0087] This embodiment provides a core particle gravity flow deposition film, and the preparation method of the core particle gravity flow deposition film comprises the following steps:

[0088] (1) Crushing, grinding and screening the core particles in sequence to obtain core nanoparticles with a particle size of 1000 nm;

[0089] Wherein, the grinding speed is 300r / min, and the grinding time is 240min;

[0090] (2) ultrasonically mixing water and the core nanoparticles obtained in step (1) at a ratio of 30 mL:0.1 g to obtain a suspension;

[0091] The ultrasonic mixing time is 30 min, the power is 80 W, and the frequency is 30 kHz;

[0092] (3) The suspension obtained in step (2) was transferred to a quartz plate with a size of 2.5 cm × 4 cm, and after being allowed to settle and dried, a quartz plate with a thickness of 3.5 × 10 5 nm core particle gravity flow deposition film;

[0093] The transferring comprises: extracting 1.0 to 3.0 mL of the suspension obtained in step (2), and injecting the extract onto the solid matrix plate at a rate of 1.5 mL / min;

[0094] The temperature of the static precipitation is 20° C. and the time is 22 hours. During the static precipitation, the solid matrix plate is placed horizontally.

[0095] The electron microscope image of the gravity flow deposited film of the core particles provided in this embodiment is as follows: Figure 1 shown.

[0096] Example 4

[0097] This embodiment provides a core particle gravity flow deposition film, and the preparation method of the core particle gravity flow deposition film is different from that of embodiment 3 only in that:

[0098] In this example, the core nanoparticles in step (1) were modified to 750 nm to obtain a thickness of 2.5×10 5 nm core particle gravity flow deposited film.

[0099] Example 5

[0100] This embodiment provides a core particle gravity flow deposition film, and the preparation method of the core particle gravity flow deposition film is different from that of embodiment 3 only in that:

[0101] In this example, the core nanoparticles in step (1) were modified to 500 nm to obtain a thickness of 1.5×10 5 nm core particle gravity flow deposited film.

[0102] Example 6

[0103] This embodiment provides a core particle gravity flow deposition film, and the preparation method of the core particle gravity flow deposition film is different from that of embodiment 3 only in that:

[0104] In this example, the core nanoparticles in step (1) were modified to 1500 nm to obtain a thickness of 4×10 5 nm core particle gravity flow deposited film.

[0105] Example 7

[0106] This embodiment provides a core particle gravity flow deposition film, and the preparation method of the core particle gravity flow deposition film is different from that of embodiment 3 only in that:

[0107] In this example, the core nanoparticles in step (1) were modified to 2000 nm to obtain a thickness of 5.5×10 5 nm core particle gravity flow deposited film.

[0108] The height variation curve of the core particle gravity flow deposition film in the X (horizontal) direction provided by the above-mentioned Examples 3-7 is as follows: Figure 2 shown.

[0109] Example 8

[0110] This embodiment provides a core particle gravity flow deposition film, and the preparation method of the core particle gravity flow deposition film is different from that of embodiment 3 only in that:

[0111] In this example, the injection rate described in step (3) was modified to 0.5 mL / min.

[0112] Example 9

[0113] This embodiment provides a core particle gravity flow deposition film, and the preparation method of the core particle gravity flow deposition film is different from that of embodiment 3 only in that:

[0114] In this example, the injection rate described in step (3) was modified to 2 mL / min.

[0115] Comparative Example 1

[0116] This comparative example provides a core particle gravity flow deposition film, and the preparation method of the core particle gravity flow deposition film is different from that of Example 3 only in that:

[0117] In this comparative example, the screening process described in step (1) is omitted, that is, the particle size of the core nanoparticles obtained in step (1) is not unique, and the particle size range is 500 to 2000 nm.

[0118] Application Examples

[0119] The core particle gravity flow deposition film provided in the above embodiment and comparative example is used to analyze the imbibition wetting characteristics of the oil reservoir. The specific process includes the following steps:

[0120] The contact angle of the core deposited film was measured using a contact angle meter (KRUSS DSA100) using the droplet method. Each film sample was measured 5 times and the wetting angle distribution was recorded.

[0121] At the same time, using the orthogonal spatial stereo high-speed camera observation test bench, the contact angle can be observed and captured through horizontal observation; in the vertical direction, through the camera lens magnification, the ratio and size of the imaging area pixels are calibrated, the infiltration and spreading radius are calculated, and the infiltration and absorption rate are collected. The contact angle is recorded by accurately calibrating the high-speed camera in the horizontal direction.

[0122] The wetting angle values ​​of the core particle gravity flow deposited films provided in the above embodiments and comparative examples measured in the X (horizontal) direction are shown in Table 1.

[0123] Table 1

[0124]

[0125]

[0126] The wetting angle variation process captured by the core particle gravity flow deposition film provided in Example 3 of the present invention in the X (horizontal) direction is as follows: Figure 3 shown.

[0127] according to Figure 3It can be seen that the entire contact process is shown in the following process: a-the droplet just contacts the deposited film; b-the droplet gradually penetrates into the film; c-the bottom of the droplet has infiltrated into the film; d-the droplet is dialyzed in the film. Finally, it is in a stable state, and its stable contact angle is 38.4°. By observing the changes in the behavior of the droplet throughout the process, it is found that the overall hydrophilicity of the core is strong, which is consistent with the characteristics of the dry layer sandstone sampled before grinding.

[0128] analyze Figure 2 It can be seen that the core particle gravity flow deposited film provided by the present invention has different deposition thicknesses. As the particle size increases from 500 nm to 2000 nm, the thickness of the deposited film increases from about 1.5×10 5 Increased to 5.5×10 5 nm, indicating that with the increase of particle size, the film particles form a skeleton structure with different characteristics, and the core particle molecules with larger particle size have a larger stacking height after deposition. At the same time, it can be observed from the surface roughness that the same type of film has very small fluctuations in the vertical direction. Under the reference deposition plane, the average fluctuation height is about 300nm and the maximum fluctuation height is about 500nm, indicating that the surface roughness of the deposited film is very small and the flatness is high.

[0129] In summary, the core particle gravity flow deposition film provided by the present invention can realize the accurate analysis of the imbibition characteristics of reservoir cores, and has broad application scenarios in the field of reservoir wettability and imbibition research.

[0130] The applicant declares that the present invention illustrates the detailed structural features of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed structural features, that is, it does not mean that the present invention must rely on the above-mentioned detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

[0131] The applicant declares that the present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a core particle gravity flow deposition film, characterized in that: The preparation method comprises the following steps: (1) grinding and screening the core particles in sequence to obtain core nanoparticles; (2) mixing water and the core nanoparticles obtained in step (1) to obtain a suspension; (3) The suspension obtained in step (2) is transferred to a solid matrix plate, and after static precipitation and drying, the core particle gravity flow deposition film is obtained.

2. The preparation method according to claim 1, characterized in that: The grinding process in step (1) also includes a crushing process; Preferably, the weight ratio of the core particles to the grinding balls in the grinding is 3:(4-6); Preferably, the grinding speed is 300-500 r / min; Preferably, the grinding time is 240 to 280 minutes; Preferably, the particle size of the core nanoparticles in step (1) is 500 to 3000 nm.

3. The preparation method according to claim 1 or 2, characterized in that: The ratio of water to core nanoparticles in step (2) is 30 mL: (0.1-0.5) g; Preferably, the mixing in step (2) comprises ultrasonic mixing; Preferably, the ultrasonic mixing time is 20 to 40 minutes; Preferably, the power of the ultrasonic mixing is 80 to 120 W; Preferably, the frequency of the ultrasonic mixing is 30-50 kHz.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The size of the solid matrix plate in step (3) is (2-3) cm×(3-5) cm; Preferably, the solid substrate plate in step (3) comprises any one of quartz, hydrophilic glass or quartz glass.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The transferring in step (3) comprises: extracting the suspension obtained in step (2) and injecting it onto the solid matrix plate; Preferably, the extraction volume of the suspension is 1.0 to 3.0 mL.

6. The preparation method according to claim 5, characterized in that: The instrument used in the transfer in step (3) includes a dual-channel pump or a syringe; Preferably, the injection rate is 0.8-1.5 mL / min.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The temperature of the static precipitation is 20-30°C; Preferably, the solid matrix plate is placed horizontally during the static sedimentation; Preferably, the static sedimentation time is 22 to 28 hours.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The preparation method comprises pre-treating the solid matrix plate in step (3); Preferably, the pretreatment comprises: washing and drying the solid matrix plate in sequence.

9. A core particle gravity flow deposition film, characterized in that: The core particle gravity flow deposition film is obtained by the preparation method according to any one of claims 1 to 8; The thickness of the core particle gravity flow deposition film is 1.5×10 5 ~5.5×10 5 nm.

10. An application of the core particle gravity flow deposition film as claimed in claim 9, characterized in that: The core particle gravity flow deposition film is used to detect and analyze the dialysis wetting characteristics of the oil reservoir.

Citation Information

Patent Citations

  • Surface enhanced raman scattering activity nanometer porous metal substrate and method for making same

    CN101216430A

  • Materials and methods for controlling properties of organic light-emitting device

    CN102842686A

  • Method for the production of electrodes for fully solid batteries

    CN104011905A

  • Polystyrene microsphere deposition method

    CN115896743A

  • Porous polymer membrances, methods of making, and methods of use

    WO2012058154A2